"I have a dream" the vividness effect in international business communication. (7th July 2021) - Brunzel, Johannes; von der Oelsnitz, Dietrich
Abstract : Purpose: The so-called vividness effect, painting a verbal picture to an audience and a key element of charismatic rhetoric, provides opportunities to make corporate communication more persuasive. The article seeks to provide evidence regarding: (1) the presence of the effect in written, international business communication and (2) whether vivid communication by top-level executives affects perception of their communication effectiveness. Design/methodology/approach: The article employs a qualitative, exploratory setting (focus groups) to examine the attitude of participants towards vivid communication of top-executives. The article also employs a computer-aided-content-analysis (CATA) in two of the most important stock indices (Deutsche Aktienindex and Dow Jones) from 2011 to 2015 to locate the presence of the rhetorical style in annual reports. Lastly, the article studies via a quasi-experimental approach whether this type of communication is perceived differently on the dimensions of communication effectiveness by Segars and Kohut (2001) using unique 485 responses from recruited US-citizens. Findings: The article reveals empirically that companies make use of this type of communication across stock indices. The results of the conformational, quasi-experimental study (Study 3) suggests that vividness is perceived differently by an audience. Therefore, positive attributional effects are not univocally related to communication effectiveness but to the dimensions responsibility and customer commitment. The participants also attribute other desirable characteristics towards the speaker, thereby providing evidence for a partial positive effect of vividness on communication effectiveness. Originality/value: The article employs an established measure of communication effectiveness and combines it with a key communication style from academia and industry. In addition, the article combines several methods to examine the construct (mixed-models).